EXPRESSION OF THE CONCEPT OF FORGIVENESS IN LEXICOGRAPHIC SOURCES AND ARTISTIC LITERATURE - Khazratqulova, Ozoda (Ижтимоий-гуманитар фанларнинг долзарб муаммолари / Актуальные проблемы социально-гуманитарных наук / Actual Problems of Humanities and Social Sciences., 2024)
This article is written about the expression of the concept of forgiveness in lexicographical sources and literary works. Proverbs contain insight, experience, wisdom, and truth, and are thus thought to represent ready-made traditional strategies in oral speech acts and from high literature to mass media.